ANALISIS DAYA DUKUNG DAN PENURUNAN PONDASI BORED PILE METODE LUCIANO DECOURT & PROGRAM PLAXIS 2D - Jatmiko, Muhammad Fauzi; Abidin, Farhan Zainul; Firmansyah, Yerry Kahaditu (Jurnal Teknik Sipil dan Arsitektur, 2026)
The demand for reliable transportation infrastructure requires accurate evaluation of foundation performance, particularly for deep foundations such as bored piles used in elevated road structures. This study aims to analyze the bearing capacity and settlement behavior of bored pile foundations at point P4 of the Kediri–Tulungagung Toll Road Project, specifically on the Access Road to Dhoho Airport. Subsurface investigations indicate a soil profile dominated by clay at shallow depths and loose to dense sand at deeper layers, necessitating detailed analysis of strength and deformation characteristics. The analytical approaches employed include the empirical Luciano Decourt method and numerical modeling using PLAXIS 2D based on the finite element method. The bearing capacity analysis of the P4 bored pile using the Luciano Decourt method resulted in an allowable capacity (Qijin) of 354.26 tons and an ultimate capacity (Qult) of 885.65 tons. Meanwhile, the settlement analysis performed using PLAXIS 2D yielded a value of 45.98 mm, which closely matches the empirical settlement of 41.7 mm. The difference of approximately 10% demonstrates good agreement between the two methods. The results confirm that the bored pile foundation at point P4 is capable of supporting the design load of 764.8 tons, with the measured settlement remaining within acceptable limits. The integration of empirical and numerical methods enhances the reliability of the evaluation and provides a more comprehensive understanding of soil–structure interaction. This combined approach has been proven effective and can serve as a reference for foundation design in similar infrastructure projects. Keyword : Bored Pile, Bearing Capacity, Settlement Analysis, PLAXIS 2D